PROBLEMATIKA ANAK DALAM PENYESUAIAN DIRI - Harbeng Masni (Jurnal Ilmiah Dikdaya, 2017)
Abstract : Social beings is a predicate attached to humans, the status remains as beings who would not be able to live alone this earth. One is not born in a state able to adapt, physical condition, mentally and emotionally influenced and directed by environmental factors. Adjustment is one important requirement for the creation of psychiatric or mental health of an individual. Perfect adjustment occurs when a human being or an individual is always in a state of balance between itself and its surroundings where there is no longer a need that is not met, and in which all the functions of the organism / individual running normally. In addition to environmental factors, psychological factors, maturity, physical condition, and culture also affect the process of adjustment. Adjustment problems facing children can be derived from the psychological atmosphere of the family as a family rift. Besides problems will arise for the adjustment of children who often move to another place. The school environment also has a great influence on the development of adolescent life. Megemban school besides teaching function is also a function of education. At school, the teacher should be able to be more effective, such as a fair, honest, fun and so on so that students will feel happy and safe with him.Keywords: Problems, Adjustment